Akhlak dalam Perspektif Islam: Analisis Konseptual tentang Klasifikasi Moral, Prinsip Baik-Jahat, dan Perilaku Manusia - Cut Nadiatul Husna; Hayati Hayati (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
The growing complexity of contemporary social life has intensified scholarly attention to Islamic moral values as an ethical foundation for individual and social conduct. While discussions on akhlak have been extensively developed, studies that systematically integrate the classification of akhlak, the principles of good and evil, and their implications for human behavior within a unified conceptual framework remain limited. This study aims to examine the classification of akhlak in Islam, analyze the Islamic principles that distinguish good from evil, and explore their relevance to human behavior. A qualitative library research approach was employed by examining classical and contemporary literature, including books, scholarly articles, and academic publications related to Islamic ethics. The collected data were analyzed using qualitative content analysis through data reduction, categorization, interpretation, and synthesis. The findings demonstrate that Islamic morality is structured around akhlak mahmudah and akhlak mazmumah, with both categories originating from the spiritual condition of the individual. The study further reveals that the standards of good and evil are derived from the Qur'an and the Sunnah, providing an objective ethical framework that guides human conduct. These findings reinforce the significance of moral education, exemplary practice, and character formation in strengthening individual integrity while responding to contemporary moral challenges from an Islamic perspective.